Experiment on Ability to Understand Three Dimensional Material Concepts Related to Learning Styles Using the Geogebra-Supported STAD Learning Model - Sugianto, Rahmad; Darmayanti, Rani; Amany, Diella Aprilani Luthfia; Rachmawati, Lelly Nur; Hasanah, Siti Nur; Aji, Fauzan Bayu (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
The abstract nature of mathematical objects makes learning mathematics difficult and many students experience difficulties in learning mathematics. The purpose of this study was to determine the effect of the Geo - Gebra- assisted STAD learning model on the ability of students' mathematical understanding of learning styles. This study uses a quasi-experimental research method. The population of this study were students of SMA in the 2015/2016 academic year. The research sample was taken by cluster random sampling. The sample size is 64 students, consisting of 34 students in the experimental class and 30 students in the control class. As a research instrument , the researcher conducted a mathematics learning achievement test and a learning style questionnaire. Data were analyzed using two-way ANOVA. The conclusions of this study are: Geogebra- assisted STAD -type collaborative learning model Winplot produces better mathematical comprehension abilities and mathematics learning achievement compared to PowerPoint-assisted direct learning models. Students with a visual learning style are at the same level as students with an auditory learning style. Students with an auditory learning style are at the same level as students with a kinesthetic learning style. Students with a visual learning style perform better in school than students with a kinesthetic learning style.